Reactive Ion Etching (RIE) Induced Surface Roughness Precisely Monitored In-Situ and in Real Time by Reflectance Anisotropy Spectroscopy (RAS) in Combination with Principle Component Analysis (PCA) - Emerson Oliveira; Johannes Strassner; Christoph Doering; Henning Fouckhardt (Advances in Materials Science and Engineering)
Reactive ion etching (RIE) of group IV or III/V semiconductors is an important step in many lithographic processes in semiconductor technology. Typically, surface roughness is undesired, but more and more applications arise where rough surfaces are used as functional quasi-layers. Either to avoid roughness or to precisely define it, in situ monitoring and control of the state of the etch front is desirable to increase yield. As we already know, reflectance anisotropy spectroscopy (RAS) or RAS equipment might be used to monitor the state of the etch front, to determine the current etch depth in situ precisely with accuracies of as good as some lattice constants only, and to identify roughness morphologies, the latter in combination with principle component analysis (PCA) and linear discriminant analysis (LDA). In cases where only one specific morphology with different characteristic parameters is under consideration, PCA suffices for monitoring, although the task is even harder. The PCA-RAS combination allows for distinguishing states of the etch front, which differ by a couple of minutes of etch duration only.